Análises química e microbiológica de solo em sistemas agroflorestais - Pina, Iara Jaime de (2016)
Agroforestry Systems (AFS) are forms of land use that consort, in time and space, the production of forest species with agricultural and/or animals. Several studies attest to the potential of these systems to improve soil quality. Therefore, there is an initiative in implementing these systems in the settlement Maria Lara, located in Centenário do Sul, Paraná. This study aimed to evaluate the behavior of chemical and microbiological variables of the soil before and after the development of the agroforestry systems . For this, each SAF was divided into 04 plots of 7,5x10 meters each, in which it was collected 02 soil samples (0-10 and 10-20 cm depth) in november 2014, february, april, august and october 2015. We evaluated the density of fungi, including mycorrhizal microrrízicos fungi, bacteria, pathogenic and free living nematodes, microbial biomass carbon (Cmic), pH (CaCl2), H + Al, organic matter content soil, P, Ca, Mg, K, SB and CEC. The design was admitted in incomplete blocks, in a factorial 3x2x5, being factors: three SAF (AFS1, AFS 2 and AFS 3); two soil sampling depths (0-10 cm and 10-20 cm) and five times (T0, T1, T2, T3 and T4), each treatment had four replications. A multivariate approach by Variance Multivariate Analysis was made with Variable Analysis Canonical (AVC) of the factors. The microbiological variables soil responded better than chemical variables against the management carried out in the AFS. At the end time of the study, it was observed that, in the three AFS, increase Ca, Mg, SB and CTC and increased pH. In SAF1 also noted average increases in the levels of P and K. There were no significant increases in organic matter content for AFS2 and AFS3, but there was a reduction of this variable to the AFS1. For microbiological variables observed average increases to free-living and plant pathogenic nematodes, mycorrhizal microrrízicos fungi, Scutellospora heterogama, bacteria, Penicillium sp., Aspergillus sp. and Cmic.